2015
DOI: 10.1177/1938640015592840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality, Accuracy, and Readability of Online Resources Pertaining to Hallux Valgus

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 25 publications
5
36
2
Order By: Relevance
“…However, only the difference between DISCERN scores of the videos shared by physicians and those shared by non-physicians reached statistical significance (p<0.001). Similarly, previous studies have also found that quality of the medical information published by physicians was higher than the medical information published by non-physicians [23]. In our study, scores given to the question about reliability and treatment information in the DISCERN scoring system were also higher in the videos shared by physicians compared to the videos shared by non-physicians.…”
Section: Discussionsupporting
confidence: 82%
“…However, only the difference between DISCERN scores of the videos shared by physicians and those shared by non-physicians reached statistical significance (p<0.001). Similarly, previous studies have also found that quality of the medical information published by physicians was higher than the medical information published by non-physicians [23]. In our study, scores given to the question about reliability and treatment information in the DISCERN scoring system were also higher in the videos shared by physicians compared to the videos shared by non-physicians.…”
Section: Discussionsupporting
confidence: 82%
“…However, many internet sources are not regulated or edited, resulting in the dissemination to patients of an overwhelming amount of content that may be low quality and inaccurate. [3][4][5][6] Therefore, it is imperative for physicians to be aware of and critically evaluate such resources to help educate patients and guide them through the management of their disease such that they are not misinformed.…”
mentioning
confidence: 99%
“…12,20 Admittedly, the web has become more accessible than ever before, which likely accounts for the increased use in our cohort; only 1 of the 36 (3%) patients who did not use the Internet in our study cited a lack of access as the reason.…”
Section: Discussionmentioning
confidence: 68%